Anaerobic fermentation of gelatinized sago starch-derived sugars to acetone—1-butanol—Ethanol solvent by Clostridium acetobutylicum - A. A., Madihah; Ariff, A. B.; Khalil, M. S.; Karim, M. I. A.; M. S., Suraini (Springer, 2001)
A study of the kinetics and performance of solvent-yielding batch fermentation of individual sugars and their mixture derived from enzymic hydrolysis of sago starch by Clostridium acetobutylicum showed that the use of 30 g/L gelatinized sago starch as the sole carbon source produced 11.2 g/L total solvent, i.e. 1.5-2 times more than with pure maltose or glucose used as carbon sources. Enzymic pretreatment of gelatinized sago starch yielding maltose and glucose hydrolyzates prior to the fermentation did not improve solvent production as compared to direct fermentation of gelatinized sago starch. The solvent yield of direct gelatinized sago starch fermentation depended on the activity and stability of amylolytic enzymes produced during the fermentation. The pH optima for α-amylase and glucoamylase were found to be at 5.3 and 4.0-4.4, respectively. α-Amylase showed a broad pH stability profile, retaining more than 80% of its maximum activity at pH 3.0-8.0 after a 1-d incubation at 37°C. Since C. acetobutylicum α-amylase has a high activity and stability at low pH, this strain can potentially be employed in a one-step direct solvent-yielding fermentation of sago starch. However, the C. acetobutylicum glucoamylase was only stable at pH 4-5, maintaining more than 90% of its maximum activity after a l-d incubation at 37°C.